Mechanismen der Zelltodregulation - Oliver Metzig, Marie; Gdynia, Georg; Roth, Wilfried (Der Pathologe, 2012)
During tumorigenesis cancer cells acquire certain features allowing for sustained growth and circumvention of programmed cell death. For decades cancer research has been focused on the molecular mechanisms of apoptosis and how to overcome apoptosis resistance in tumor cells. Meanwhile, novel types of programmed cell death have turned out to be important for both physiological and pathological processes. Recent findings imply that induction of alternative forms of programmed cell death, such as necroptosis, might be used as a therapeutic approach to overcome therapy resistance in cancer.